Creative Product Development Strategies in a Dunia Fantasi Ancol - Nugraha, Rizki Nurul; Setyawati, Irma; Awaloedin, Dipa Teruna (West Science Interdisciplinary Studies, 2024)
This research explores creative product development strategies in Dunia Fantasi Ancol through a qualitative approach. Using qualitative research methods, this research uses observation and interview analysis. The research results reveal that Dunia Fantasi Ancol emphasizes collaboration with creative artists, in-depth market research and innovation to create unique and attractive products. Through regular meetups and creative platforms, they keep local artists, designers and creators engaged. Strict supervision throughout the production process is carried out to maintain high quality standards, and continuous adjustment to market trends and visitor feedback ensures product appeal. This strategy proved its success through increased visits, positive feedback, and growth in creative market share. This research provides in-depth insight into how Dunia Fantasi Ancol achieves success in developing its creative products.